Broiler Chicken Sales Forecasting Using Holt’s Double Exponential Smoothing at UD Annisa Sidabutar - Alwam Sidabutar; Ali Hadomuan Hasibuan; Hery Sunandar (Jurnal Armada Informatika, 2026)
Month-to-month fluctuations in broiler chicken sales make it difficult for UD Annisa Sidabutar to determine proportional inventory levels. Decisions based solely on experience may cause excess stock during low-demand periods or shortages when demand increases. This study applies Holt’s Double Exponential Smoothing method to forecast broiler chicken sales using 12 monthly observations from July 2025 to June 2026. The method was selected because the series fluctuates and exhibits a changing tendency, while the available observations are insufficient to estimate a robust annual seasonal pattern. Smoothing parameters were calibrated by testing 81 combinations of alpha and beta ranging from 0.1 to 0.9 at 0.1 intervals. The best combination was alpha 0.9 and beta 0.1, producing a Mean Absolute Percentage Error of 28.60%, a Mean Absolute Error of 197.70 units, and a Root Mean Squared Error of 287.19 units. Using the selected model, sales are projected at 732 units in July 2026 and increase gradually to 1,066 units in June 2027. The forecasts can serve as an initial reference for inventory planning; however, they should be interpreted cautiously because the historical series covers only one year and contains several sharp fluctuations.